Hemiepiphysiodesis: when should it be considered a day-case procedure?. Issue 1 (January 2021) - Barrett, Matthew C.; Manoukian, Dimitrios; Tzatzairis, Themistoklis; Segaren, Neil; Firth, Gregory. B.; Ramachandran, Manoj
Abstract : Hemiepiphysiodesis is usually planned as a day-case but patients may stay overnight for pain control. In this study, we assessed the required level of analgesia (LOA) and length of stay (LOS) in patients undergoing hemiepiphysiodesis about the knee joint. We conducted a retrospective cohort study of patients that underwent temporary hemiepiphysiodesis of the distal femur or proximal tibia using hemiepiphysiodesis plates (eight-plates) for coronal plane deformities between January 2012 and October 2019. Demographics, type of procedure, anatomical site, anaesthetic time, preoperative, intraoperative and postoperative analgesia, and time of surgery were collected. Anterior hemiepiphysiodesis and permanent drill epiphysiodesis procedures were excluded. In this series of 79 patients, those with increased American Society of Anesthesiologists Score >1 and patients that were operated on >2 sites required increased LOA, ( P < 0.05) and prolonged LOS ( P < 0.05). The timing of surgery (morning vs. afternoon list) did not influence LOS or LOA. Patient-controlled analgesia (PCA) was required in 8 of 14 (57%) patients with four growth plates operated on. All ( n = 12) patients that received PCA remained in hospital for at least one night. The use of local infiltration intraoperatively played a significant role in early discharge of the patients and t lower the LOA postoperatively ( P < 0.05). Parameters including the number of growth plates operated on, use of tourniquet and intraoperative local infiltration can independently influence LOS and LOA postoperatively and at discharge. These parameters should be taken into consideration when consulting with the patient and family and when planning the postoperative course.